Design of Information Systems Reporting Employment in Dinas Tenaga Kerja of Surabaya - Pratiwi, Nila Elzha; Setyawan, Henry Bambang; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Annual Employment Report is part of the Company's existing functions at the Department of Labor Surabaya, inspection, implementation, assessment and monitoring of employment. In doing compulsory reporting are currently several issues, namely: the length of the processing and preparation of reports so that the limited information available, the lack of facilities in approving compulsory reporting. The solution to these problems is to create an information system capable of managing reporting labor required to report the data into information that can be used to provide a policy on employment. These employment information reporting system can be easier for companies to perform compulsory reporting companies every year, can facilitate in approving compulsory reporting company, can assist in addressing the recording and processing of data shall be reported.